Improvement of Yield of Bean Grown on Inceptisol Jatinangor Applied with Granular Organic Fertilizer and Harvest Interval - Kusumiyati Kusumiyati; Sutari Wawan; Syarief Aanisah Lutfiyyah; Oktavia Ade Risti (JOURNAL OF TROPICAL SOILS, 2018)
Low bean production in Indonesia is caused by several factors such as poor soil condition and low quality of the pods. The use of granular organic fertilizer can optimize soil as a growing medium of beans. In addition, the application of harvest interval setting in combination with the use of granular organic fertilizer probably can  improve production and quality bean pods. The research aimed to find out granular organic fertilizer doses and harvest interval setting that resulted in good effects on the growth, yield, and quality of beans grown on Inceptisol from Jatinangor, West Java. A field experiment was carried out at Ciparanje field, Jatinangor, West Java from February to April 2016. The experiment was arranged in a Randomized Block Design (RBD) with 12 treatments and 3 replications. The results showed that the dose of 150 kg ha-1 granular organic fertilizer and harvest interval of every two days resulted in shoot:root ratio of 12.8, increased percentage of productive branches up to 57.48%, increased percentage of grade B pods (60.17%) and lowered the percentage of grade C pods (29.21%).